# Idiotic Mathematical Proofs

#### danarhea

##### Slayer of the DP Newsbot
DP Veteran
Just thought I would start a thread in which people could put idiotic mathematical items. Here is an interesting application of the mangling of mathematical laws:

take 2 numbers a and b. a is equal to b.

a=b

1) Multiply both sides of the equation by the same number and both sides are still equal (axiom of multiplication):

a**2=ab

2) Subtract both sides of the equation by the same number and both sides are still equal (axiom of subtraction):

a**2-b**2=ab-b**2

3) Factoring yields

(a+b)(a-b)=b(a-b)

4) Multiply both sides of the equation by the same number and both sides are still equal (axiom of multiplication):

(a+b)(a-b)(a-b)**-1=b(a-b)(a-b)**-1

5) Canceling out like terms yields

a+b=b

Therefore 2=1

Of couse, there is an obvious mistake in this theorem, which is easy to find. LOL.

#### Kelzie

##### The Almighty
DP Veteran
danarhea said:
Just thought I would start a thread in which people could put idiotic mathematical items. Here is an interesting application of the mangling of mathematical laws:

take 2 numbers a and b. a is equal to b.

a=b

1) Multiply both sides of the equation by the same number and both sides are still equal (axiom of multiplication):

a**2=ab

2) Subtract both sides of the equation by the same number and both sides are still equal (axiom of subtraction):

a**2-b**2=ab-b**2

3) Factoring yields

(a+b)(a-b)=b(a-b)

4) Multiply both sides of the equation by the same number and both sides are still equal (axiom of multiplication):

(a+b)(a-b)(a-b)**-1=b(a-b)(a-b)**-1

5) Canceling out like terms yields

a+b=b

Therefore 2=1

Of couse, there is an obvious mistake in this theorem, which is easy to find. LOL.

I got a mistake. Not sure if that's the one you're referring too....2a only equals ab if a and b equal 2. If they equaled say 6, you'd have to multiply it by 6 to be a correct application of the axiom of multiplication. You had:

(6) x 2= (6)(6)

Not true.

#### Connecticutter

##### Active member
Let's start by changing ** to ^ in order to denote exponentiation.

Okay, now we can go through the steps:

a = b (Given)
aa = ba (Multiplication by both sides)
a^2 = ba (Changing aa to a squared)
a^2 - b^2 = ba - b^s (Subtraction on both sides)
(a+b)(a-b) = b(a - b) (Factoring - completely legal)
(a+b) = b (Canceliing a-b)***
a = 0 (Subtraction)

***Here's the problem:
a - b is zero, and so our conclution is equivalent to this:
If a*0 = b*0, then a = b by "cancelling" out the zero.
Of course, that's completely ridiculous.

These are fun. I'll put down another one later.

#### OnionCollection

##### Member
yes its effectively 1x0 = 2x0 which is true

and then tries to do

1 = (2x0)/0

which isnt

#### Thorgasm

##### Bus Driver to Hell
DP Veteran
danarhea said:
Just thought I would start a thread in which people could put idiotic mathematical items. Here is an interesting application of the mangling of mathematical laws:

take 2 numbers a and b. a is equal to b.

a=b

1) Multiply both sides of the equation by the same number and both sides are still equal (axiom of multiplication):

a**2=ab

2) Subtract both sides of the equation by the same number and both sides are still equal (axiom of subtraction):

a**2-b**2=ab-b**2

3) Factoring yields

(a+b)(a-b)=b(a-b)

4) Multiply both sides of the equation by the same number and both sides are still equal (axiom of multiplication):

(a+b)(a-b)(a-b)**-1=b(a-b)(a-b)**-1

5) Canceling out like terms yields

a+b=b

Therefore 2=1

Of couse, there is an obvious mistake in this theorem, which is easy to find. LOL.

First of all, in this proof a=b=1.
The mistake is when you cancel terms you are dividing by (a-b). (a-b)=0 in this proof. Dividing by zero is the precise mistake. Dividing by zero is illegal.

#### danarhea

##### Slayer of the DP Newsbot
DP Veteran
independent_thinker2002 said:
First of all, in this proof a=b=1.
The mistake is when you cancel terms you are dividing by (a-b). (a-b)=0 in this proof. Dividing by zero is the precise mistake. Dividing by zero is illegal.

Bingo. Give the man a cigar. However, you will never be able to refute the proof that 1+1=3. My son is living proof of that one. Hehe.

T

#### The Real McCoy

Proof that women are evil:

We know that women require time & money so..

Women = Time X Money

And of course, time is money...

Time = Money

Therefore...

Women = Money X Money

or..

Women = Money^2

Now, since money is the root of all evil...

Money = (square root of Evil)

..and after squaring both sides of the equation to get rid of the square root...

Money^2 = (square root of Evil)^2

or simply..

Money^2 = Evil

and since we determined...

Women = Money^2

we come to the conclusion that...

Women = Evil